Clinicopathological profile and survival in children with parameningeal rhabdomyosarcoma in resource-limited settings: A single-center experience from Uganda - Richard Nyeko; Fadhil Geriga; Racheal Angom; Joyce Balagadde Kambugu; Jaques van Heerden (PLoS ONE, 2025)
Background Parameningeal rhabdomyosarcoma (PM-RMS) represents a diagnostic and therapeutic challenge, especially in low- and middle-income countries (LMICs), given its location and its propensity for local and intracranial extension. This study determined the clinical and pathological profile and survival in children with PM-RMS treated at a single tertiary cancer treatment facility in Uganda. Methods This was a retrospective study involving a review of records of children and adolescents aged below 18 years with rhabdomyosarcoma treated at the Uganda Cancer Institute (UCI) between January 2016 and December 2020. Kaplan-Meier survival analysis and Cox’s proportional hazards model were used for five-year survival analysis. Results We identified 32 PM-RMS cases with a median age of 4.8 years (range 1–15 years). The most common tumor sites were the infratemporal region (25.0%), middle ear (21.8%), and nasopharynx (18.8%). Most patients (90.6%) were IRS group III, and 34.4% had regional lymph node involvement. Embryonal and alveolar histologies represented 46.9% and 21.8%, respectively, with 31.3% unclassified. Nearly all patients (90.6%) received chemotherapy, but only 43.8% underwent radiotherapy for local control. One- and five-year overall survival rates were 65% and 12%, respectively. Regional nodal involvement and receipt of local control were the significant predictors of survival (adjusted HR 4.61 and 6.07, respectively). Conclusion Our study demonstrates a low survival rate among children with PM-RMS among the patient cohort, and treatment abandonment remains high. Regional nodal involvement and local control significantly predicted survival.